1985
DOI: 10.1128/iai.49.3.700-708.1985
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Staphylococcus aureus clumping factor

Abstract: Immunochemically identical components were isolated from water-soluble phases of five Staphylococcus aureus strains by affinity chromatography on fibrinogen-linked Sepharose 4B. The elution was performed with 1 M MgCl2. The component could be isolated from sonicated preparations of whole cells, cell walls, and extracellular products of S. aureus but not from sonicated preparations of staphylococcal L-forms or from Staphylococcus epidermidis. Investigations of the eluted component by immunoelectrophoresis and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…The high antibody response after immunization with C F could also be a consequence of the structure of this molecule. Analysis of C F showed a high content of polysaccharide by weight (9). C F had a relative molecular mass (M,) of about 400,000 and showed only one band on SDS-page under reduced condition (9).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The high antibody response after immunization with C F could also be a consequence of the structure of this molecule. Analysis of C F showed a high content of polysaccharide by weight (9). C F had a relative molecular mass (M,) of about 400,000 and showed only one band on SDS-page under reduced condition (9).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of C F showed a high content of polysaccharide by weight (9). C F had a relative molecular mass (M,) of about 400,000 and showed only one band on SDS-page under reduced condition (9). It was suggested that C F is composed of repeated units of minor glycopeptides interlinked by bindings not broken by SDS in the presence of P-mercaptoetha-no1 (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations